Recent Advances in Geotechnical Research - Wu, Wei (Springer Series in Geomechanics and Geoengineering,, 2019)
This book provides a snapshot of the research activities of the Institute of Geotechnical Engineering, University of Natural Resources and Life Sciences in Vienna, Austria. The topics are broad ranged including: · Centrifuge model testing · Constitutive model · Granular physics · Numerical simulation · Soil bioengineering The topics reflect our geotechnical research in a changing world. Traditional topics in foundation engineering are fading out and new topics are emerging. The European Commission is gratefully acknowledged for funding the following projects within its program FP7 and Horizon2020: MUMOLADE (Multiscale modelling of landslide and debris flow), REVENUES (Reinforced Vegetation Numerical Evaluation of Slopes) and GEORAMP (Geohazards - Risk Assessment, Mitigation and Prevention).